Diptera, Ceratopogonidae Newman, 1834: new records of biting and predaceous midges from Iberá wetlands, Argentina - Spinelli, Gustavo Ricardo (2012)
The first Argentina records of four species of biting and predaceous midges (Diptera: Ceratopogonidae) are provided from the Iberá wetlands in Corrientes Province: Forcipomyia (Euprojoannisia) unica Bystrak and Wirth, Echinohelea blantoni Wirth, Neobezzia fittkaui Wirth and Ratanaworabhan and Paryphoconusgrandis Macfie. This is the first record of the predaceous midge genus, Echinohelea Macfie, from Argentina. © 2012 Check List and Authors.